2013
DOI: 10.1111/jmft.12051
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Professional Gains of Master's Level Students Following a Person‐of‐the‐Therapist Training Program: A Retrospective Content Analysis

Abstract: The Person-of-the-Therapist Training (POTT) is a program designed to facilitate clinicians' ability to consciously and purposefully use themselves at the moment of contact with their clients in order to connect, assess, and intervene effectively. This qualitative study explored the experiences of 54 master's-level students who were enrolled in an accredited marriage and family therapy program in the United States and examined their perceived professional gains following a 9-month POTT course. Content analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…Although MFT trainees report that addressing SOT issues is an important component of training (Lutz & Spell Irizarry, 2009;Niño et al, 2013), it is unclear if trainees learn to use self effectively. Philp and Geldard (2011) studied experiences of learning social constructionist therapy models and discovered that students believe that they use self in limited ways when learning and using social constructionist therapies.…”
Section: Training the Self Of The Therapistmentioning
confidence: 98%
See 1 more Smart Citation
“…Although MFT trainees report that addressing SOT issues is an important component of training (Lutz & Spell Irizarry, 2009;Niño et al, 2013), it is unclear if trainees learn to use self effectively. Philp and Geldard (2011) studied experiences of learning social constructionist therapy models and discovered that students believe that they use self in limited ways when learning and using social constructionist therapies.…”
Section: Training the Self Of The Therapistmentioning
confidence: 98%
“…However, MFTs must also learn to use themselves to facilitate interventions and develop relationships with clients (Aponte & Carlsen, 2009). The therapist's personal role in clinical practice is often referred to as the "person" or "self" of the therapist (Niño, Kissil, & Apolinar Claudio, 2013), and training environments can provide opportunities for self of the therapist (SOT) work (Aponte & Carlsen, 2009;Timm & Blow, 1999). Family therapists have focused on the SOT since the birth of the field , and many MFTs consider SOT work an essential component of therapist development and training (Lum, 2002;Timm & Blow, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…EFT focuses on the understanding and expression of emotions as one of the central mechanisms for therapeutic change (Furrow, Edwards, Choi, & Bradley, 2012;Johnson, 2004). In relation to POTT, awareness of one's emotional processing while in the presence of clients, enhanced capacity to experience one's emotions, and better management of one's emotional responses to clients, were some of the professional gains reported by master's level students who had participated in POTT (Niño et al, 2015). POTT trainees described these gains in emotional processing as central to the improvement of their clinical skills because these changes allowed them to be more empathically present with their clients and be better able to regulate their emotional responses (Niño, Kissil, & Cooke, 2016;Niño et al, 2015).…”
Section: Conceptual Similarities Between Pott and Eftmentioning
confidence: 99%
“…We stumbled upon this study while conducting another study on the professional benefits that trainees reported resulting from the Person of the Therapist Training ([POTT]; Niño, Kissil, & Apolinar Claudio, ). We noticed that many students reported personal changes they have undergone as a result of the training and we were impressed.…”
Section: Person‐of‐the‐therapist Trainingmentioning
confidence: 99%
“…Two recent studies on POTT support the perceived effectiveness of the training (Niño, Kissil, & Cooke, ; Niño et al, ). Findings suggest that key outcomes of the training are congruent with its stated goals.…”
Section: Person‐of‐the‐therapist Trainingmentioning
confidence: 99%